CREATE-ing New Perspectives: A Transformative Learning Approach to Sustainability in First-Year Engineering Education - Swartz, Bronwyn (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This paper examines how integrating challenge-based/problem-based learning (CBL/PBL) with creative expression triggers perspective transformation in first-year engineering students' understanding of sustainability. The Crafting Resourceful Engineering and Artistic Transformations for Education (CREATE) project, framed by Mezirow's Transformative Learning Theory, used artistic creation as a disorienting dilemma to challenge preexisting assumptions about engineering's role in sustainability while developing ECSA Graduate Attributes. Funded by South African Society for Engineering Education (SASEE), the project engaged students with SDGs through four interconnected assessments: individual essays and presentations, group artistic artifacts and TikTok videos. First-year engineering students consulted with a Fine Arts student on project designs, creating interdisciplinary collaborations that challenged traditional engineering paradigms. Longitudinal survey data revealed evidence of perspective transformation aligned with Mezirow's theory. Students progressed from viewing sustainability as isolated technical problems to understanding it as interconnections between society, technology, and environment. This shift was evident in their enhanced ability to communicate technical concepts while considering broader societal implications—a key indicator of transformative learning in engineering education.